Amplifying The Character Education and The Multiculturalism for a Nationalism Building - Thoriquttyas, Titis (TADRIS: Jurnal Pendidikan Islam, 2017)
Abstract: In recent decade, the number of mass – violence, discrimination and disintegration in the national scale are increasing so that it needful the immediately solution, one of the ways through the education. Lately, the character education and its implementation on multicultural society become the national and global issues. It closely related to the real challenges which faced by the society today about the student population in Indonesia becomes more culturally diverse. From the brief explanation above, this paper is focused on the multiculturalism, the nationalism, the character education and Islamic education. Furthermore, this study aims to uncover and explore the model of character education on Islamic education and its significance potentially with Indonesia’s multicultural ideals. In concluding, the researcher believed that the multicultural spirit is able to shape by the formulation of character education.  Keywords: Multiculturalism; Character Education; Nationalism